Crystal structure of ethyl (2S, 2′R)-1′-benzyl-3-oxo-3H-dispiro[1-benzothiophene-2, 3′-pyrrolidine-2′, 11′′-indeno[1, 2-b]quinoxaline]-4′-carboxylate. (March 2015) - Govindaraj, J.; Raja, R.; Suresh, M.; Raghunathan, R.; SubbiahPandi, A.
No abstract available